Low-Temperature Superplasticity and Deformation Mechanism of Ti-6Al-4V Alloy - Zhou, Ge (Materials (Basel), 2018)
The low-temperature superplastic tensile behavior and the deformation mechanisms of Ti-6Al-4V alloy are investigated in this paper. Through the experiments carried out, elongation to failure (δ) is calculated and a set of values are derived that subsequently includes the strain rate sensitivity exponent (m), deformation activation energy (Q) at low-temperature superplastic deformation, and the variation of δ, m and Q at different strain rates and temperatures. Microstructures are observed before and after superplastic deformation. The deformation mechanism maps incorporating the density of dislocations inside grains at temperatures of 973 and 1123 K are drawn respectively. By applying the elevated temperature deformation mechanism maps based on Burgers vector compensated grain size and modulus compensated stress, the dislocation quantities and low-temperature superplastic deformation mechanisms of Ti-6Al-4V alloy at different temperatures within appropriate processing regime are elucidated.